Development and application of a 1K functional liquid chip for lactation performance in Bactrian camels - Guo, Lili; Dao, Lema; Liu, Bin; Wang, Jingyu; Liu, Zaixia; Ma, Fengying; Morigen, Bielige; Chang, Chencheng; Bai, Yinbatu; Guo, Yaqiang; Shi, Caixia; Cao, Junwei; et al. (Frontiers in Veterinary Science, 2024)
Introduction The advancement of high-throughput, high-quality, flexible, and cost-effective genotyping platforms is crucial for the progress of dairy breeding in Bactrian camels. This study focuses on developing and evaluating a 1K functional liquid single nucleotide polymorphism (SNP) array specifically designed for milk performance in Bactrian camels. Methods We utilized RNA sequencing data from 125 lactating camels to identify and select 1,002 loci associated with milk production traits for inclusion in the SNP array. The array’s performance was then assessed using 24 randomly selected camels. Additionally, the array was employed to genotype 398 individuals, which allowed for population validation to assess the polymorphism of SNP sites. Results The SNP array demonstrated high overall SNP call rates (> 99%) and a remarkable 100% consistency in genotyping. Population validation results indicate that camels from six breeding areas in Northwest China share a similar genetic background regarding lactation functionality. Discussion This study highlights the potential of the SNP array to accelerate the breeding process of lactating Bactrian camels and provides a robust technical foundation for improving lactation performance.